2014
DOI: 10.1090/s0025-5718-2014-02813-5
|View full text |Cite
|
Sign up to set email alerts
|

Analysis on a generalized algorithm for the strong discrete logarithm problem with auxiliary inputs

Abstract: We investigate a recently proposed algorithm solving the strong discrete logarithm problem with auxiliary inputs, and show that this algorithm in general is not more efficient than ordinary discrete-logarithm-solving algorithms such as Pollard’s rho method, by analyzing a lower bound on the sum of digits of integers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…However, the recent result of Kim et al [14] shows that the complexity of the several generalizations in the case where d | Φ k (p) for k 3 [7,20] is always greater than p 1/2 . Therefore, we need to consider a different approach to solving the DLPwAI.…”
Section: Algorithm Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the recent result of Kim et al [14] shows that the complexity of the several generalizations in the case where d | Φ k (p) for k 3 [7,20] is always greater than p 1/2 . Therefore, we need to consider a different approach to solving the DLPwAI.…”
Section: Algorithm Descriptionmentioning
confidence: 99%
“…Subsequently, several generalizations of this algorithm have attempted to solve the problem when d is a divisor of Φ k (p) for the kth cyclotomic polynomial Φ k (x) [7,14,20]. Satoh [20] generalized the algorithm, using the embedding of α ∈ F p into the general linear group GL k (F p ).…”
Section: The Discrete Logarithm Problem With Auxiliary Inputsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the efficiency of the algorithm was not well-studied. Kim [11,12] studied Satoh's generalization of the +1 algorithm for solving the DLP-wAI. The result showed that the complexity of Satoh's algorithm was not faster than Cheon's algorithm when | ( ) and ≥ 3.…”
Section: Mathematical Problems In Engineeringmentioning
confidence: 99%
“…However, its complexity for k ≥ 3 was not clearly understood. Recently, Kim et al [24] realized that Satoh's generalization is essentially the same as the embedding of F p into F p k , and clarified the complexity of the algorithm. Unfortunately, their result suggests that, in most cases, the complexity of this generalization is not faster than the current square-root complexity algorithm, such as Pollard's rho algorithm [31], for k ≥ 3.…”
Section: Introductionmentioning
confidence: 99%